2018
DOI: 10.1089/jpm.2017.0179
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use in the Last Days of Life in Hospital, Hospice, and Home Settings in the Netherlands

Abstract: Patients who die an expected death receive many medications in the last week of life, part of which are preventive medications. Medication management in patients' final days of life can be improved, especially in the hospital and home setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…30,31 Therefore, patients and informal carers are often charged with managing a great number of medications, with different routes of administration, prescribed for a variety of reasons, and often involving powerful drugs with a high risk of adverse side effects. 29,32 Arevalo et al 33 identified that seven days before death the mean number of medications being taken by patients was nine. Importantly on the day of death, 27% of patients used a preventative medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Therefore, patients and informal carers are often charged with managing a great number of medications, with different routes of administration, prescribed for a variety of reasons, and often involving powerful drugs with a high risk of adverse side effects. 29,32 Arevalo et al 33 identified that seven days before death the mean number of medications being taken by patients was nine. Importantly on the day of death, 27% of patients used a preventative medication.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming clear within the literature that much greater understanding of polypharmacy is needed to understand why prescribing focus may not shift from the active management of comorbidities and chronic disease with such preventative medications to the provision of comfort care and effective control of symptoms at the end of life. 29,33,34 Professional respondents in the study by Dees et al 29 highlighted issues such as not wanting to diminish patients' hope, being unwilling to have difficult end-of-life conversations, and an emphasis on prescribing being the role and responsibility of a lead physician, as reasons for not undertaking the rationalization of unnecessary medications.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of EOL medications, our study showed in the last 3 days of life, charting of opioids was 87%, benzodiazepines 73% and antipsychotics 43%, which compares favourably with a retrospective cohort study of three RACFs in Norway, that showed on the last day of life, Morphine was charted in 71.4%, Midazolam 55% and Haloperidol 46.9% [ 50 ]. In terms of administration of EOL medications, there have been two recent retrospective cohort studies from the Netherlands, one conducted in a PCU [ 51 ] and another conducted in hospital, hospice and home settings [ 52 ]. These studies of the last days of life, have measured the proportion of use of specific medications, types of medications (palliative vs preventative) and medication classes, the total amount given in milligrams each day and route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Experts in our study gave specific suggestions for research and development. Whereas a substantial part of medications in end-of-life care are prescribed for comorbid diseases, 16 there is an urge for reflection on how to manage those medications at the end of life and to address this issue in treatment guidelines. Pharmacological guidelines rarely give any recommendations for discontinuation.…”
Section: What This Study Addsmentioning
confidence: 99%